DnaK and GroEL chaperones are recruited to the Bacillus subtilis membrane after short-term ethanol stress - Seydlová, G; Halada, P; Fišer, R; Toman, O; Ulrych, A; Svobodová, J (Journal of applied microbiology, 2012)
AIMS: To find out membrane tolerance strategy to ethanol in Bacillus subtilis that possesses a powerful system of protection against environmental stresses. METHODS AND RESULTS: Cytoplasmic membranes of B. subtilis were severely affected by even short-term exposure to 3% (v/v) ethanol: the growth rate and membrane protein synthesis were markedly reduced, and no adaptive alterations in phospholipids were detected. Simultaneously, steady-state DPH fluorescence anisotropy (r(ss)) showed that the membrane rigidity increased substantially. Analysis of the membrane phosphoproteome using in vitro labelling with [γ-(32) P]ATP revealed the association of DnaK and GroEL chaperones with membrane, indicating a stress induction process. Upon a long-term 3% (v/v) ethanol stress, the cell growth accelerated slightly and the composition of polar head groups and fatty acids of membrane phospholipids underwent an extensive reconstruction. Correspondingly, membrane fluidity turned back to the original r(ss) values of the control cells. CONCLUSIONS: In B. subtilis, the adaptive response to short-term ethanol stress comprises the recruitment of molecular chaperones on the impaired membrane structure; consequently, the phospholipid synthesis is restored and membrane fluidity adapts properly to the continuing ethanol stress. SIGNIFICANCE AND IMPACT OF THE STUDY: These findings underline the role of membrane lipids in establishing tolerance towards ethanol and also suggest the contribution of molecular chaperones to the membrane and cell recovery.
Keywords: buněčná membrána; fluidita membrány; fyziologický stres; Bacillus subtilis; molekulární chaperony; Fluorescence Polarization; membránové lipidy; ethanol; bakteriální proteiny; Molecular Chaperones; Stress, Physiological; mastné kyseliny; fluorescenční polarizace; Phospholipids; Membrane Fluidity; Bacterial Proteins; fosfolipidy; Cell Membrane; Ethanol; Membrane Lipids; Fatty Acids